PENGARUH KUALITAS LAYANAN TERHADAP LOYALITAS PELANGGAN DALAM MENGGUNAKAN TRANSPORTASI ONLINE PADA MAHASISWA UNIVERSITAS KADIRI - Pramana, Andy Chandra; Yap, Nonni; Prasaja, Mukti (Universitas Nusantara PGRI Kediri, 2021)
The rise of online transportation business today makes online transportation businesses scramble for consumer loyalty. Loyalty is a situation where consumers view positively a product or service provider company accompanied by continuous and consistent reuse of such services or products. Loyalty is formed because of customer satisfaction in obtaining product services both goods and services. Customer satisfaction can be formed from the quality of good service from service providers. The purpose of this study was to see the influence between the quality of service and customer loyalty in using online transportation with student respondents at Kadiri University. The type of research used is quantitative research with data collection through questionnaires. Variables in the study consisted of independent variables and dependent variables. Independent variable is the quality of service from Parasuraman et,al. namely tangible, reability, responsiveness, assurance and empathy. While the dependent variable in this study are customer loyalty. Multiple regression analyses are used to test the influence between independent and dependent variables. The conclusion of the research shows that simultaneously, the quality of service positively affects customer loyalty in using online transportation with a value of Sig < 0.05. While for partial influence, tangible dimensions, reability, responsiveness and assurance have a sig asim value of Sig < 0.05 so as to show a significant risk to customer loyalty. While the empathy dimension has a value of asim Sig > 0.05 so it has no effect on customer loyalty.